Analysis of the Economic Performance of ASEAN Countries from a Public Accountability Perspective Based on ASEAN Key Figures 2025 - Yulia Yunita Yusuf; Adriansyah Adriansyah; Anisatun Humayrah Rais (Universitas Negeri Makassar, 2026)
This research analyzes the economic performance of ASEAN countries from the perspective of public accountability based on ASEAN Key Figures 2025. Using a comparative descriptive quantitative method, macroeconomic indicators are evaluated as a reflection of development outcomes and public accountability. The results show that ASEAN's aggregate performance is very strong in 2024, although unevenly distributed. Indonesia dominates total GDP, Vietnam leads in economic growth, while Singapore excels in GDP per capita, trade in services, and FDI. In conclusion, the comparison of these macroeconomic indicators serves as crucial non-financial information to evaluate the effectiveness of each member country's development policies.